Mandibular third molar autotransplantation in a 15-year-old patient: five-year radiographic and clinical follow-up case report - Marampa, Wilman Rante; Herdiani, Mirsa; Samad, Syahril; Agustin, Sylvia (Padjadjaran Journal of Dentistry, 2025)
ABSTRACT Introduction: Tooth autotransplantation is a viable treatment option for replacing extracted permanent teeth that have been damaged due to caries, trauma, and malformations. This method offers a quick and economical solution when a donor tooth is available to replace a non-restorable tooth. The purpose of this case report is to present a unique case of mandibular third molar autotransplantation performed in a 15-year-old patient, with five-year radiographic and clinical follow-up. Case report: A 15-year-old female patient presented with her parents to the emergency room at Abdul Wahab Sjahranie Regional Hospital, complaining of an unbearable toothache following a previous dental filling. Intraoral examination revealed tooth 46 with a glass ionomer cement (GIC) restoration, a positive percussion test, and no history of swelling. An orthopantomogram (OPG) examination showed a radiolucent area at the apex of tooth 46. Impacted tooth 48 was observed with periodontal tissue in good condition and an incompletely formed root. Autotransplantation was performed using tooth 48 after the extraction of tooth 46. At the five-year follow-up appointment after treatment, tooth 48 remained stable and fully functional, with no complications, including mobility or infection. Conclusion: Tooth autotransplantation is an effective option for replacing missing teeth in young patients. Long-term success can be achieved with appropriate patient selection, atraumatic surgical technique, and careful postoperative care.KEYWORDSMandible, immature teeth, third molars, autotransplantation, extraction